Food in transition: university students' discourse about food practices - Lin, Yin-Ling (2010)
Little is known about the food practices of UK university students. 'Student food' often carries a negative connotation of being 'improper' or 'unhealthy'. This thesis investigates the accounts of food practices offered by undergraduate students at the University of Nottingham.